ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN KREATIF MATEMATIS SISWA BERKEMAMPUAN MATEMATIKA TINGGI DI SEKOLAH MENENGAH PERTAMA (Studi Kualitatif di Masa Pandemi Covid-19) - Humairah Muztika, - (2021)
This is a descriptive qualitative research study aims to determine how mathematical critical thinking and creative thinking abilities with high mathematics ability in junior high school. Five high mathematics ability students in class VIII at one of Junior High Schools in Dumai city at the 2020/2021 academic year were subjects of this study. Instrument used in this research were a mathematical critical thinking ability test, a mathematical creative thinking ability test, and interviews. Analysis in this study includes data reduction, data presentation, and verification. High mathematics ability students did not have all characteristics of indicators for mathematical critical thinking and creative thinking skills. High mathematics ability students in general already have the characteristics of indicators critical thinking ability focus and inference. On the indicators of mathematical creative thinking skills, high mathematics ability students are already having characteristics indicator of flexibility. The results of this study can be used as a basis for finding model solutions or learning methods that can develop students' critical and creative mathematical thinking skills in SPLDV material during the covid-19 pandemic using online learning.